Targeting the mesenchymal subtype in glioblastoma and other cancers via inhibition of diacylglycerol kinase alpha. Issue 2 (29th June 2017) - Olmez, Inan; Love, Shawn; Xiao, Aizhen; Manigat, Laryssa; Randolph, Peyton; McKenna, Brian D; Neal, Brian P; Boroda, Salome; Li, Ming; Brenneman, Breanna; Abounader, Roger; Floyd, Desiree; et al.
Abstract: Background: The mesenchymal phenotype in glioblastoma (GBM) and other cancers drives aggressiveness and treatment resistance, leading to therapeutic failure and recurrence of disease. Currently, there is no successful treatment option available against the mesenchymal phenotype. Methods: We classified patient-derived GBM stem cell lines into 3 subtypes: proneural, mesenchymal, and other/classical. Each subtype's response to the inhibition of diacylglycerol kinase alpha (DGKα) was compared both in vitro and in vivo. RhoA activation, liposome binding, immunoblot, and kinase assays were utilized to elucidate the novel link between DGKα and geranylgeranyltransferase I (GGTase I). Results: Here we show that inhibition of DGKα with a small-molecule inhibitor, ritanserin, or RNA interference preferentially targets the mesenchymal subtype of GBM. We show that the mesenchymal phenotype creates the sensitivity to DGKα inhibition; shifting GBM cells from the proneural to the mesenchymal subtype increases ritanserin activity, with similar effects in epithelial-mesenchymal transition models of lung and pancreatic carcinoma. This enhanced sensitivity of mesenchymal cancer cells to ritanserin is through inhibition of GGTase I and downstream mediators previously associated with the mesenchymal cancer phenotype, including RhoA and nuclear factor-kappaB. DGKα inhibition is synergistic with both radiation and imatinib, a drug preferentially affecting proneural GBM. Conclusions: Our findings demonstrate that a DGKα–GGTase I pathway can be targeted to combat the treatment-resistant mesenchymal cancer phenotype. Combining therapies with greater activity against each GBM subtype may represent a viable therapeutic option against GBM.